2020
DOI: 10.3892/mmr.2020.11189
|View full text |Cite
|
Sign up to set email alerts
|

Identification of co‑expression modules and hub genes of retinoblastoma via co‑expression analysis and protein‑protein interaction networks

Abstract: retinoblastoma is a common intraocular malignant tumor in children. However, the molecular and genetic mechanisms of retinoblastoma remain unclear. The gene expression dataset GSe110811 was retrieved from Gene expression omnibus. after preprocessing, coexpression modules were constructed by weighted gene coexpression network analysis (WGcna), and modules associated with clinical traits were identified. In addition, functional enrichment analysis was performed for genes in the indicated modules, and protein-pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 47 publications
0
6
0
Order By: Relevance
“…A growing number of studies have identified DEGs during hypoxia in different cancer cell types using RNA-Seq analysis [ 3 - 5 ] . However, their findings only represent the genetic characteristics of specific tumor cells during hypoxia.…”
Section: Introductionmentioning
confidence: 99%
“…A growing number of studies have identified DEGs during hypoxia in different cancer cell types using RNA-Seq analysis [ 3 - 5 ] . However, their findings only represent the genetic characteristics of specific tumor cells during hypoxia.…”
Section: Introductionmentioning
confidence: 99%
“…A system-based approach is needed to gain a comprehensive view of cancer, and the power of differential co-expression networks was previously shown in cancer research ( Gov and Arga, 2017 ) . The construction and analysis of differential co-expression networks have been widely used to discover gene modules and hub genes in various cancers, including retinoblastoma ( Mao et al, 2020 ), pituitary adenoma ( Aydin and Arga, 2019 ), ovarian ( Gov and Arga, 2017 ; Gov, 2020 ), lung ( Liao et al, 2020 ) , and cervical cancers ( Kori et al, 2019 ) .…”
Section: Introductionmentioning
confidence: 99%
“…Though it is standard practice to perform enrichment analysis using pathway and gene set databases (e.g. KEGG and Gene Ontology ( 19 )) on gene lists from co-expression networks such as those from a particular disease module ( 20 , 21 ) for mechanistic insights, this approach ignores the topology of the network as it exclusively relies upon sets of genes rather than the network structure. In a recent study, Paci et al.…”
Section: Introductionmentioning
confidence: 99%